Understanding the Concept of Photo Electricity: Applications and Implications in Quantum Physics - Subandi, Yunita Kristianti; Sulastri, Endang; Bukangdonu, Feronika; Yohakim, Yoman Ribeta Ratu; Jufriansah, Adi; Sahlan (Bincang Sains dan Teknologi, 2024)
This research investigates the photoelectric effect using PhET Simulation to verify and test hypotheses related to this phenomenon. The study focuses on the interaction between ultraviolet (UV) light and sodium electrodes, analyzing the relationship between light wavelength and the resulting electron energy. Through experiments, critical constants in physics, such as Planck's constant, are calculated to validate the theories of the photoelectric effect. The findings demonstrate a non-linear relationship between UV light wavelength and current strength, with optimal photon energy required to induce maximum electron ejection at specific wavelengths. This research highlights the significance of simulation tools in understanding quantum physics concepts and aims to enhance teaching methods for more effective and engaging physics education.